Penggunaan Model Pembelajaran Discovery Learning Berbantuan Media PhET Simulation untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Materi Asam Basa - Cilin L Sutiono; Ani Sutiani (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the effect of discovery learning model assisted by PhET simulation media on students' motivation and learning outcomes in acid-base material, and to determine the correlation between the two variables. The study used a quantitative approach with a quasi-experimental type and a pretest–posttest control group design. The study sample consisted of two grades of eleventh grade at SMA Negeri 1 Percut Sei Tuan which were selected randomly, namely the experimental class and the control class. The research instruments were a learning outcome test and a learning motivation questionnaire. The results showed that the increase in students' learning motivation in the experimental class was in the high category (N-Gain = 0.78), while the control class was in the medium category (N-Gain = 0.48). The increase in students' learning outcomes in the experimental class was also higher (N-Gain = 0.79) than the control class (N-Gain = 0.54). The results of the hypothesis test showed that there was a significant difference in motivation and learning outcomes between the experimental class and the control class (sig. <0.05). In addition, there was a positive and significant correlation between learning motivation and learning outcomes with a correlation coefficient of 0.577 which was included in the medium category. Based on the research results, the discovery learning model assisted by PhET simulation significantly improved student motivation and learning outcomes in acid-base topics.